PERLINDUNGAN HAK MASYARAKAT ADAT PAPUA DALAM KERANGKA OTONOMI KHUSUS - Muhammad Musaad (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
The implementation of Law Number 21 of 2001 concerning Special Autonomy for the Papua province should be a means for the protection and empowerment of the rights of the Papuan indigenous peoples to natural resources. However, since Papua returned to the lap of the Unitary State of the Republic of Indonesia, these rights have not been fulfilled. This paper discusses how efforts can be made to improve this situation within the framework of the Special Autonomy status for Papua Province. This study uses a qualitative approach with descriptive analysis in presenting the research results. The analysis of the research results provides an overview of the dynamics of the process of drafting the Special Autonomy Law for the Province of Papua. Second, how the Papua Special Autonomy Law can protect the rights of the indigenous peoples of Papua province by analyzing the factors that enable indigenous peoples to exercise their rights effectively.